Medicinal herbal mixture for the treatment of oral diseases - K. A. Zavadich; E. A. Smolyarchuk; N. V. Kudashkina; S. S. Sologova; B. B. Sysuev; O. I. Stepanova; S. V. Averyanov; L. V. Kornopoltseva; V. S. Shchekin; A. V. Samorodov; A. A. Yusupova; A. I. Shubina (Разработка и регистрация лекарственных средств, 2025)
Introduction. The use of synthetic drugs is associated with a number of side effects. When choosing a therapy to correct symptoms and treat dental diseases such as stomatitis, periodontitis, gingivitis, cheilitis, it is preferable to use herbal medicines in combination with traditional therapy, which would improve the resistance of periodontal tissues to pathogenic microorganisms. Herbal preparations are highly effective and well tolerated, which allows them to be used in modern medicine.Aim. To develop a medicinal collection with antimicrobial, anti-inflammatory, and wound-healing effects.Materials and methods. The following substances and reagents were used as research materials: Achilleae millefolii herba, Bidentis tripartitaе herba, Alni fructus, Anisi vulgaris fructus in a ratio of 1 : 1 : 1 : 1, diclofenac sodium, ascorbic acid, phosphate buffer, sodium citrate, luminol, iron (II) sulfate, heparinized blood, zymosan, saline solution, 2 % formalin solution, 10 % neutral formalin solution, hematoxylin, eosin. Antimicrobial activity was studied by comparing growth retardation of pathogenic microorganisms, antioxidant activity was studied on a chemoluminometer HLM-003 (Russia), hematological tests on mice were carried out using the ImageJ software package, Sysmex KX-21N (Sysmex, Japan), Leica RM 2145 microscope (Leica Biosystems Nussloch GmbH, Germany), binocular microscope Leica CME (Leica Biosystems Nussloch GmbH, Germany).Results and discussion. The evaluation of the anti-inflammatory, antioxidant, wound healing and antimicrobial activities of the plant herbal mixture was carried out. According to the results of the experiment, it was found that the herbal mixture has moderate antioxidant, wound healing and pronounced anti-inflammatory activity comparable to the comparison drug.Conclusion. A herbal mixture has been developed that has anti-inflammatory, antimicrobial and regenerating effects.